Optimization of Triola Plc. Loyalty Programme - Wachtlová, Dominika; Stříteský, Václav; Dohnal, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The aim of this thesis is to suggest optimizations for Triola Plc. loyalty program based on theoretical understanding of loyalty and its role in success of a company, as well as numer-ous practical analyses. The thesis is divided into two main parts. The first part overviews the theoretical knowledge about consumer loyalty and how loyalty program can be an ef-fective tool in building said loyalty. The second part is formed of variety of practical anal-yses, including analysis of Triola sales data, data mining analysis using MML-TGI data ana-lyser, consumer survey and lastly benchmarking analysis. The last chapter is a synthesis of the theoretical and practical parts and suggest recommendations for Triola loyalty program based on the insights gathered throughout the whole thesis.
Vedoucí práce: Václav Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses